Bereavement Among Adult Siblings: An Examination of Health Services Utilization and Mental Health Outcomes. Issue 12 (3rd August 2021) - Gazibara, Tatjana; Ornstein, Katherine A; Gillezeau, Christina; Aldridge, Melissa; Groenvold, Mogens; Nordentoft, Merete; Thygesen, Lau Caspar
Abstract: We aimed to examine the association of young and middle-aged sibling bereavement with use of health services and risk of developing mental health disorders over 24 months before and after sibling's death. All persons aged 18–56 years who died of illness/natural causes between 2009 and 2016 were identified in the Danish Register of Causes of Death. The study sample included 31, 842 bereaved siblings and 31, 842 age- and sex-matched controls. Overall, the largest effect was observed for increased use of psychological services: For women, the peak was observed 4–6 months after the death (odds ratio (OR) = 3.31, 95% confidence interval (CI): 2.85, 3.85) and for men in the first 3 months after the death (OR = 2.63, 95% CI: 2.06, 3.36). The peak of being diagnosed in a hospital setting with any mental disorder for women was observed in the period 13–15 months after sibling death (OR = 1.52, 95% CI: 1.11, 2.07) and for men in the first 3 months after the death (OR = 1.75, 95% CI: 1.32, 2.32). Young and middle-aged adults who experienced the death of a sibling are more likely to use health services and are at risk of poorer mental health outcomes. During the bereavement process, young and middle-aged siblings are especially in need of mental health support, such as professional psychological counseling.